International Pediatric Otolaryngology Group (IPOG) consensus recommendations: Diagnosis, pre-operative, operative and post-operative pediatric choanal atresia care. (August 2019) - Moreddu, Eric; Rizzi, Mark; Adil, Eelam; Balakrishnan, Karthik; Chan, Kenny; Cheng, Alan; Daniel, Sam J.; de Alarcon, Alessandro; Hart, Catherine; Hartnick, Christopher; Inglis, Andrew; Leboulanger, Nicolas; et al.
Abstract: Objective: To provide recommendations to otolaryngologists and allied physicians for the comprehensive management of young infants who present with signs or symptoms of choanal atresia. Methods: A two-iterative delphi method questionnaire was used to establish expert recommendations by the members of the International Otolaryngology Group (IPOG), on the diagnostic, intra-operative, post-operative and revision surgery considerations. Results: Twenty-eight members completed the survey, in 22 tertiary-care center departments representing 8 countries. The main consensual recommendations were: nasal endoscopy or fiberscopy and CT imaging are recommended for diagnosis; unilateral choanal atresia repair should be delayed after at least age 6 months whenever possible; transnasal endoscopic repair is the preferred technique; long term follow-up is recommended (minimum one year) using nasal nasofiberscopy or rigid endoscopy, without systematic imaging. Conclusion: Choanal atresia care consensus recommendations are aimed at improving patient-centered care in neonates, infants and children with choanal atresia.